USE OF ONLINE RESOURCES IN THE EDUCATIONAL PROCESS DURING TENNIS LESSONS (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents a theoretical analysis of electronic educational resources that contribute to improving the learning process during tennis training sessions. A theoretical analysis of electronic educational platforms is conducted, highlighting their role in enhancing learning efficiency through visualization, interactivity, and accessibility of materials. Various categories of digital tools are described, including multimedia presentations, video lessons, interactive trainers, mobile applications, and augmented and virtual reality technologies, which significantly improve the understanding and assimilation of technical and tactical aspects of tennis.Special attention is given to the role of video materials in learning stroke techniques, movements, and court positioning, as well as game analysis through slow-motion playback and frame-by-frame review. The possibilities of using interactive simulators and virtual trainers for developing proper motor skills are also considered. Additionally, the importance of analytical platforms for analyzing players’ tactical actions and making real-time adjustments is emphasized.The article highlights that integrating online resources into the learning process not only enhances athletes' technical training but also fosters their strategic thinking, motivation, and overall interest in tennis. The use of digital technologies allows the adaptation of educational material to the individual needs of students, ensuring flexibility and accessibility in learning.The advantages of visualization in tennis training include improved understanding of techniques (the use of video materials and animations allows for a detailed examination of technical elements such as strokes, positions, and movements on the court), error analysis and correction (online resources with slow-motion playback or frame-by-frame review help identify and correct technical deficiencies), and the development of tactical thinking (schemes and diagrams of player positioning in various game situations contribute to a better understanding of game tactics). The article explores the use of online resources in the educational process during tennis training sessions.
Keywords: Online resources; material visualization; tennis lessons; platforms; multimedia presentations; simulators; virtual and augmented reality; strategy